2011
DOI: 10.1002/clc.20840
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Epicardial Fat Measured by 64‐Multidetector Computed Tomography and Coronary Artery Disease

Abstract: Background: Epicardial fat (EF) is the visceral fat of the heart deposited under the visceral layer of the pericardium and has the same origin as abdominal visceral fat, which is shown to be strongly related to the development of coronary artery disease (CAD). We measured the volume of EF (EFV) by 64-multidetector computed tomography (MDCT) and studied the relationship between EFV and the severity of CAD. Hypothesis: Epicardial fat volume increases steeply in patients with significant coronary artery stenosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 22 publications
3
48
1
Order By: Relevance
“…Iwasaki et al also observed, on a univariate analysis, a higher EFV in patients with significant coronary stenosis (>50%) compared to patients without CAD. 16 Also, Ueno et al have shown that EFV is independently related to chronic total occlusions. 17 The Framingham Heart Study found an association between EAT and CCS in a cross-sectional analysis, but only when including the adipose tissue in addition to traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Iwasaki et al also observed, on a univariate analysis, a higher EFV in patients with significant coronary stenosis (>50%) compared to patients without CAD. 16 Also, Ueno et al have shown that EFV is independently related to chronic total occlusions. 17 The Framingham Heart Study found an association between EAT and CCS in a cross-sectional analysis, but only when including the adipose tissue in addition to traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays MDCT is preferred to echocardiography because volumetric EAT measurement by MDCT is found to be more reliable than echocardiographic thickness measurement [4]. Previous studies showed a strong correlation between EAT volume measured by MDCT and cardiometabolic risk factors [14], coronary calcium score [15], and CAD [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…MDCT can provide more accurate measurements than other techniques because of its high temporal resolution [1], and MDCT measurements are reproducible [2,3]. It has also been shown that MDCT volumetric measurements are more reliable than echocardiographic thickness measurements [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Cardiology, Iwasaki et al reported on the relationship between EAT, the calcium score, and the severity of coronary atherosclerosis. 3 They studied 197 patients who underwent CT calcium scoring and 64-slice CT coronary angiography. In all of these patients they carefully measured the volume of EAT using a dedicated off-line postprocessing program.…”
mentioning
confidence: 99%
“…124 cm 3 . The volume of EAT accounts for approximately 15% to 20% of the total cardiac volume and covers approximately 80% of the total cardiac surface.…”
mentioning
confidence: 99%